Intelligent control testing system for researching intertidal benthos based on wireless network - ZHANG HAIFENG; CAO YIJIANG; ZHOU JING; HE QIANG; YANG YANG; CAO QIEMU; FENG JUMENG (2012)
An intelligent control testing system for researching intertidal benthos based on a wireless network comprises a plurality of intelligent control testing devices, the wireless network and a computer terminal. Each intelligent control testing device is connected with the computer terminal through the wireless network and comprises a liquid level sensor, a lighting lamp, a lighting sensor, a rainfall simulating device, a fan, a first heater, a second heater, a refrigerator, a water temperature sensor, an air temperature sensor, a rock mass, a wave making pump, a draining pump, saline water, a water vat, a magnetic three-way valve and a micro-programmed control unit (MCU) microprocessor. The intelligent control testing system is wide in application prospect and high in accuracy, can be applied to research of seaweed and the intertidal benthos, and can simulate natural environment, such as oceans and lakes through reasonable combination of application software and hardware so as to enable people to conveniently f